2015
DOI: 10.5194/hess-19-1385-2015
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of extreme floods based on CMIP5 climate models: a case study in the Beijiang River basin, South China

Abstract: Abstract. The occurrence of climate warming is unequivocal, and is expected to be experienced through increases in the magnitude and frequency of extreme events, including flooding. This paper presents an analysis of the implications of climate change on the future flood hazard in the Beijiang River basin in South China, using a variable infiltration capacity (VIC) model. Uncertainty is considered by employing five global climate models (GCMs), three emission scenarios (representative concentration pathway (RC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 37 publications
1
29
0
Order By: Relevance
“…An approach to real-time prediction of oods generated by overtopping failure in natural dams was developed by Ma and Fu [220]. Studies of extreme oods were carried by Takeuchi [193] and Wu et al [188].…”
Section: Floodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An approach to real-time prediction of oods generated by overtopping failure in natural dams was developed by Ma and Fu [220]. Studies of extreme oods were carried by Takeuchi [193] and Wu et al [188].…”
Section: Floodsmentioning
confidence: 99%
“…Due to climate warming, extreme precipitation is expected to be more intense and frequent [188], which may lead to oods and other natural disasters such as landslides. Also, other hydrologic processes, such as snowmelt, can increase the occurrence of oods [189][190].…”
Section: Floodsmentioning
confidence: 99%
“…Similar conclusions were drawn recently by Xiao et al (2013) for the West River, the Yujiang River, the Guijiang River, Hongshuihe River, and the North River (Beijiang) using five different GCMs under RCP4.5. Only Wu et al (2014) yielded different conclusions; they found low likelihood of increasing treads in high flow under the RCP4.5 scenario in the North River. Decreases in annual average low flows are projected for the whole basin.…”
Section: Impact Of Changes In River Discharge On Water Resourcesmentioning
confidence: 97%
“…In terms of future climate change, some studies preferred hypothetical climate change scenarios (Jiang et al, 2007;Li et al, 2011). Few studies used the output of GCMs to force the hydrological models in the Pearl River Basin (Liu et al, 2012;Wu et al, 2014;Xiao et al, 2013). However, more attention was paid to annual discharge and extreme flood events (Wu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation